LPA5 Is an Inhibitory Receptor That Suppresses CD8 T-Cell Cytotoxic Function via Disruption of Early TCR Signaling - Mathew, Divij; Kremer, Kimberly N.; Strauch, Pamela; Tigyi, Gabor; Pelanda, Roberta; Torres, Raul M. (Frontiers in Immunology, 2019)
Persistent T cell antigen receptor (TCR) signaling by CD8 T cells is a feature of cancer and chronic infections and results in the sustained expression of, and signaling by, inhibitory receptors, which ultimately impair cytotoxic activity via poorly characterized mechanisms. We have previously determined that the LPA5 GPCR expressed by CD8 T cells, upon engaging the lysophosphatidic acid (LPA) bioactive serum lipid, functions as an inhibitory receptor able to negatively regulate TCR signaling. Notably, the levels of LPA and autotaxin, the phospholipase D enzyme that produces LPA, are often increased in chronic inflammatory disorders such as chronic infections, autoimmune diseases, obesity and cancer. In this report, we demonstrate that LPA engagement selectively by LPA5 on human and mouse CD8 T cells leads to the inhibition of several early TCR signaling events including intracellular calcium mobilization and ERK activation. We further show that, as a consequence of LPA5 suppression of TCR signaling, the exocytosis of perforin-containing granules is significantly impaired and reflected by repressed in vitro and in vivo CD8 T cell cytolytic activity. Thus, these data not only document LPA5 as a novel inhibitory receptor but also determine the molecular and biochemical mechanisms by which a naturally occurring serum lipid that is elevated under settings of chronic inflammation signals to suppress CD8 T cell killing activity in both human and murine cells. As diverse tumors have repeatedly been shown to aberrantly produce LPA that acts in an autocrine manner to promote tumorigenesis, our findings further implicate LPA in activating a novel inhibitory receptor whose signaling may be therapeutically silenced to promote CD8 T cell immunity.